Genetic variants of the glucagon-like receptor-1 in obesity - Nikulina, Anna (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Dysfunction of the glucagon-like peptide 1 (GLP-1)/GLP-1 receptor (GLP-1R) axis promotes obesity and metabolic disorders. The aim was to study the associations of the single nucleotide variants (SNV) GLP1R gene with proinflammatory cytokines and metabolic disorders in children with various obesity phenotypes. Material and methods. 252 children with obesity aged 6-18 years were examined. The first group (n=152) was represented by children with metabolically unhealthy obesity (MUO). The second group (n=100) consolidated of children with metabolically healthy obesity (MHO). Whole genome sequencing (CeGat, Germany) was performed in 52 children. Results. An association with the development of obesity was noted for T alleles rs61754624 (t=3.33) and rs10305457 (t=2.06); with MUO – for C alleles rs1042044 (t=2.23), rs1126476 (t=2.63), rs2235868 (t=2.82); T alleles rs61754624 (t=3.33), rs10305457 (t=2.06) GLP1R, p<0.05. In the MHO group, a correlation was found with the levels of pro-inflammatory markers IL-1β, IL-6 in the presence of the GA genotype SNV rs3765468; with hyperglycemia - GA genotype SNV rs6923761, CC genotype SNV rs1042044, AA rs6918287; hyperinsulinemia - GA genotype SNV rs3765468, GG rs10305421; triglyceridemia - AA rs6918287 of GLP1R. Conclusion. SNV rs1042044, rs3765468, rs6923761, s6918287, and rs rs10305421 GLP1R are associated with the development of MUO in individuals with MHO.
Human Research Ethics Committee of Dnipro State Medical University, Ukraine (meeting minutes No. 7 of December 11, 2019 and minutes from meeting No. 4 of September 2, 2020).
Keywords: analysis of single nucleotide gene variants; children; glucagon-like peptide-1 receptor; metabolically healthy obe- sity; metabolically unhealthy obesity